Reassessing Hybridisation in Australian Tetragonula Stingless Bees Using Multiple Genetic Markers - James P. Hereward; Tobias J. Smith; Ros Gloag; Dean R. Brookes; Gimme H. Walter (Ecology and Evolution, 2025)
ABSTRACT We re‐examined reports of hybridisation in three cryptic stingless bee species in the genus Tetragonula in South East Queensland, Australia (T. carbonaria, T. davenporti and T. hockingsi). Previous studies on this group using microsatellite markers proposed that hybridisation occasionally takes place. In contrast, we find that using 1745 SNPs we could reliably separate the three species, with no evidence of contemporary (or recent) hybridisation. We found identical amplicon sequences of the nuclear gene EF1alpha across most individuals of the three species, but low and moderate species‐specific polymorphisms in the nuclear gene Opsin and the mitochondrial 16S rRNA gene, respectively, with no cases of mito‐nuclear discordance at these genes. We confirm that nuclear divergence across these species is low, based on 10–26 kb of non‐coding sequence flanking EF1alpha and Opsin (0.7%–1% pairwise difference between species). However, we find mitogenomes to be far more diverged than nuclear genomes (21.6%–23.6% pairwise difference between species). Based on these comprehensive analyses of multiple marker types, we conclude there is no ongoing gene flow among the Tetragonula species of South East Queensland, despite their morphological similarity to one another and the low nuclear divergence among them. The higher resolution provided by multiple SNP markers may lead to lower estimates of contemporary hybridisation more generally.